Renal Dysfunction and hsCRP Predict Long-term Outcomes of Percutaneous Coronary Intervention in Acute Myocardial Infarction. (May 2015) - Wang, Chong-hui; Zhang, Shu-yang; Fang, Quan; Shen, Zhu-jun; Fan, Zhong-jie; Jin, Xiao-feng; Zeng, Yong; Liu, Zhen-yu; Xie, Hong-zhi
Abstract: Background: This study assessed the combined utility of estimated glomerular filtration rate (eGFR) and serum high-sensitivity C-reactive protein (hsCRP) levels to predict long-term mortality and cardiovascular outcomes of patients with acute ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI). Elevated CRP levels and renal dysfunction have both been shown to independently and jointly predict mortality and cardiovascular outcomes after PCI in the short term. However, long-term results in patients with acute STEMI undergoing PCI have not been reported. Methods: A total of 262 patients with acute STEMI undergoing primary PCI were classified at admission into quartiles according to eGFR (<60, 60–70, 70–80 and ≥80 mL·min −1 ·1.73 m −2 ) and hsCRP (<3 and ≥3 mg/L). Mortality, nonfatal myocardial infarction (MI) and major adverse cardiac events (MACEs) were compared among the groups. Results: During a median follow-up of 48.3 months, the composite of all-cause mortality and nonfatal MI (mortality + MI) was significantly higher (35.09%) in the group with the lowest eGFR compared with that of the other 3 eGFR groups (14.29%, 3.77% and 9.43%, respectively, P < 0.0001) and the group with elevated hsCRP (34.29%) versus that with hsCRP <3 mg/L (4.41%, P < 0.0001). A combined analysis showed an exaggerated hazard in patients with the lowest eGFR and highest hsCRP (hazard ratio: 44.658; 95% confidence interval: 5.955–111.890). Conclusions: Renal dysfunction and elevated hsCRP predict a high long-term incidence of MACE in patients with acute STEMI undergoing primary PCI, with the combination being of prognostic significance for long-term mortality and MI in these patients.